Low-barrier hydrogen bond powers long-range radical transfer in the metal-free ribonucleotide reductase - Abhishek Sirohiwal; Juliane John; Yury Kutin; Rohit Kumar; Federico Baserga; Vivek Srinivas; Hugo Lebrette; Maximilian C. Pöverlein; Ana P. Gamiz-Hernandez; Joachim Heberle; Müge Kasanmascheff; Martin Högbom; et al. (Proceedings of the National Academy of Sciences, 2026)
Ribonucleotide reductases (RNRs) catalyze the conversion of ribonucleotide (RNA) to deoxyribonucleotide (DNA) building blocks initiated by a long-range (>30 Å) proton-coupled electron transfer (PCET) by mechanistic principles that remain much debated. By combining multiscale quantum and classical simulations with directed mutagenesis, X-ray crystallography, and vibrational and electron paramagnetic resonance spectroscopy, we elucidate here the molecular principles underlying how metal-free RNRs initiate the long-range PCET process by creating a highly stable 3,4-dihydroxyphenylalanine (DOPA) initiator radical. We show that DOPA• is redox-tuned by a low-barrier hydrogen bond (LBHB), with a delocalized proton that provides the catalytic power for the ribonucleotide reduction. We find that the LBHB couples to an extended hydrogen-bonded network, with distant mutations resulting in the loss of radical formation, and providing key molecular insight into the long-range radical transport mechanism in RNRs. On a general level, our findings support the direct involvement of LBHB in protein chemistry and the importance of quantum effects in enzyme catalysis.